CORPORATE SOCIAL RESPONSIBILITY OF DJARUM FOUNDATION IN PREPARING INDONESIAN FUTURE LEADERS - Firma Friskila Tati; Lina Sinatra Wijaya (Universitas Lambung Mangkurat, 2019)
The progress of a country cannot be separated from the existence of human resources, but to achieve a developed country, requires the productive, creative, and innovative human resources in managing the resources in Indonesia. To create the productive human resources, the role of the government and private sectors is needed for the progress of Indonesia. Through Djarum Foundation, PT. Djarum does the Corporate Social Responsibility (CSR), one of the CSR program is giving the scholarship (Djarum Scholarship Plus) to the college student which aims to create the future leaders. The aim of this research is to find out how CSR of Djarum Foundation in preparing Indonesian future leaders and what soft skill training programs can enhance the character of leadership in character building. This research is a descriptive qualitative research which uses interview for gaining the data, the target of this research is the representative of Djarum Scholarship Plus grantees of 28th-32nd generation. The result of this study showed that in preparing and creating the Indonesian future leaders, Djarum Foundation through CSR actively conducted the soft skill training programs (Character Building, Leadership Development, and Nation Building) and the implementation programs (Community Empowerment, Competition Challenge, and International Exposure) to bring about good changes for the progress of Indonesia.Keywords: corporate social responsibility, djarum foundation, leadership, soft skill